2003
DOI: 10.4049/jimmunol.171.3.1423
|View full text |Cite
|
Sign up to set email alerts
|

Clearance ofPneumocystis cariniiin Mice Is Dependent on B Cells But Not onP. carinii-Specific Antibody

Abstract: Both CD4+ T cells and B cells are critical for defense against Pneumocystis carinii infection; however, the mechanism by which B cells mediate protection is unknown. We show that P. carinii-specific IgM is not sufficient to mediate clearance of P. carinii from the lungs since CD40-deficient mice produced normal levels of specific IgM, but were unable to clear the organisms. Using chimeric mice in which the B cells were deficient in CD40 (CD40KO chimeras) we found that clearance of P. carinii infection is delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
108
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(118 citation statements)
references
References 44 publications
(32 reference statements)
8
108
2
Order By: Relevance
“…The evidence suggests that B-cells may be important cells for the induction of inflammation following pulmonary infection with P. carinii [37]. The data presented here do not support a role for B-cells as a contributory mechanism to exacerbated inflammation, since the inflammatory profile observed in Bcell-deficient mice was similar to that in WT control animals.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…The evidence suggests that B-cells may be important cells for the induction of inflammation following pulmonary infection with P. carinii [37]. The data presented here do not support a role for B-cells as a contributory mechanism to exacerbated inflammation, since the inflammatory profile observed in Bcell-deficient mice was similar to that in WT control animals.…”
Section: Discussioncontrasting
confidence: 41%
“…This implies that the cigarette smoke-induced antibodies are instead natural antibodies against conserved bacterial targets, as have been shown to protect against nasal colonisation with H. influenzae in mice [36]. Similarly, LUND et al [37] demonstrated that mice are protected from Pneumocystis carinii in a B-cell and antibody-dependent, but antigen-specific antibody-independent, manner. It should be noted that accumulation of IgA in the airway lumen required a lower threshold of cigarette smoke exposure (once daily) than the threshold necessary for recruitment of neutrophils into the lung lumen (twice daily).…”
Section: Discussionmentioning
confidence: 99%
“…Several surface molecules on alveolar macrophages have been shown to interact with Pneumocystis, including Fc-gamma receptor, [5] complement receptor, [6] scavenger receptor, [7] mannose receptor, [8] and dectin-1. [9] TLR2 is a pattern recognition receptor recognizing a large variety of ligands such as peptidoglycan, lipoprotein, lipopeptide, and zymosan.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that both CD4 ϩ T cells and B cells contribute to protection against Pneumocystis infections (3)(4)(5)(6)(7)(8)(9)(10), but the interactive roles of these lymphocytes in host defense have not been fully defined. Previous studies from our laboratory and others have shown that reconstitution of SCID mice with primed wild-type (WT) CD4 ϩ T cells was sufficient to facilitate Pneumocystis murina (the species found in mice) clearance from their lungs (5,6,8).…”
mentioning
confidence: 99%